2010
DOI: 10.1093/heapol/czq038
|View full text |Cite
|
Sign up to set email alerts
|

Expanding health insurance coverage in vulnerable groups: a systematic review of options

Abstract: Vulnerable groups are often not covered by health insurance schemes. Strategies to extend coverage in these groups will help to address inequity. We used the existing literature to summarize the options for expanding health insurance coverage, describe which countries have tried these strategies, and identify and describe evaluation studies. We included any report of a policy or strategy to expand health insurance coverage and any evaluation and economic modelling studies. Vulnerable populations were defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…Promoting and improving the services of the National Health Insurance Scheme is a very effective strategy to improve healthcare consumption by the rural people. This finding supports similar studies in Ahafo Ano South District in Ghana [21], slum areas in Accra [6, 7, 9, 25], and South Korea [26, 27] that people with health insurance cover utilize healthcare services more than those with no health insurance cover.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Promoting and improving the services of the National Health Insurance Scheme is a very effective strategy to improve healthcare consumption by the rural people. This finding supports similar studies in Ahafo Ano South District in Ghana [21], slum areas in Accra [6, 7, 9, 25], and South Korea [26, 27] that people with health insurance cover utilize healthcare services more than those with no health insurance cover.…”
Section: Discussionsupporting
confidence: 89%
“…Access to health insurance thus comes up a game changer to significantly improve utilization of healthcare by providing financial protection against disastrous out-of-pocket healthcare expenditures. The literature establishes direct linkages between health insurance coverage and cost and actual usage of healthcare [69]. However, health insurance as a health financing option is poorly implemented in Sub-Saharan Africa [6, 10], and Ghana's recent “moderately successful” experience is held up as a model not only for the region, but also on the global arena.…”
Section: Introductionmentioning
confidence: 99%
“…50 Such initiatives seem to improve coverage in some but not all instances, 50 although substantial increases in access to facility-based births have been noted in low-income and middleincome countries. 37 …”
Section: Community-based and Social Health Insurancementioning
confidence: 99%
“…Yet, in the case of the NHIS, there is no study that has looked at how mass media exposure could play a role in promoting enrolment into the scheme. In many developed and developing countries, mass media campaigns through television, radio, print media, and the internet are considered useful in changing health behaviors and shaping attitudes towards health policy . For example, Kimani et al found that, in Kenya, women with higher exposure to print media, radio, and television are more likely to purchase health insurance than otherwise.…”
Section: Introductionmentioning
confidence: 99%